1991
DOI: 10.2337/diacare.14.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Intervention Study: Multi-Intervention Trial in Newly Diagnosed NIDDM

Abstract: IHE was of substantial benefit for the control of glycemia, significantly diminished the need for antidiabetic drugs, and reduced a cluster of risk factors but had no effect on the control of blood lipids. This could be one major reason for the failure of IHE, effective lowering of blood pressure, and clofibric acid to prevent cardiovascular complications. Clofibric acid was only effective in reducing triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 9 publications
(5 reference statements)
5
134
1
1
Order By: Relevance
“…1 and Table 2). [30][31][32][33][34][35] We summarize the key study characteristics for these studies [30][31][32][33][34][35] in Appendix Table 5. No study evaluated mortality as a primary outcome.…”
Section: Long-term Clinical Outcomesmentioning
confidence: 99%
“…1 and Table 2). [30][31][32][33][34][35] We summarize the key study characteristics for these studies [30][31][32][33][34][35] in Appendix Table 5. No study evaluated mortality as a primary outcome.…”
Section: Long-term Clinical Outcomesmentioning
confidence: 99%
“…A limited amount of research has evaluated the longer-term effects of physical activity interventions in people with Type 2 diabetes. A large prospective study reported that only 25% of people with Type 2 diabetes were still engaged with their supervised exercise programme 2 years later [16]. Two studies [14,15] reported no significant change in physical activity 12 months after giving people with Type 2 diabetes written and oral instructions for exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are expensive to develop and maintain, and they achieve poor long-term adherence. A large prospective study reported that only 25% of their Type 2 diabetic subjects were still engaged with their supervised exercise programmes after 2 years [16]. Required are alternative interventions that are effective in stimulating long-term changes in physical activity behaviour and that can be realistically implemented into current diabetes care.…”
Section: Introductionmentioning
confidence: 99%
“…The odds ratio for myocardial infarction compared to the general population for males at the age of 50-59 was 2.7, and for females 6.2 after 5 years' followup [3]. Cardiovascular diseases (32 %) were the major cause of death although clinical manifestations of this disease group represented an exclusion criterion and the average age at entry was only 46.7 (CI 46.3-47.0) years.…”
mentioning
confidence: 99%
“…The Diabetes Intervention Study (DIS) is a prospective multicentre trial of newly detected middleaged NIDDM patients classified as diet-controlled at entry into the study [3]. As previously reported [4] 15.2 % of the patients suffered from myocardial infarction and 19.8 % had died after 11 years' follow-up.…”
mentioning
confidence: 99%